Durable superpave hot-mix asphalt mixes in Kansas - Uppu, Kiran Kumar (Kansas State University, 2012)
A recent study at Kansas State University has shown that asphalt producers in Kansas are producing hot-mix asphalt (HMA) mixtures with lower asphalt contents than those in the job-mix formula. These drier mixtures are thought to be susceptible to moisture. This project evaluated the effect of asphalt content on rutting and moisture resistance of HMA. Two different mixtures and four varying asphalt contents, optimum and lower, were selected. Another large-size mixture with four varying asphalt contents was also studied. The Hamburg Wheel Tracking Device (HWTD)test (TEX-242-F) and the Kansas Standard Test-56 (KT-56), or modified Lottman test, were used to predict moisture damage and rutting potential of these mixes. All specimens tested were prepared with the Superpave gyratory compacter. Results of this study showed the drier mixtures performed better in rutting and were less susceptible to moisture.Asphalt content significantly affects the number of wheel passes in the HWTD test. The study also revealed a weak correlation between asphalt film thickness and performance test results. Thus, the effect of varying asphalt content is nonconclusive from a durability point of view. However, performance simulations using a theoretical model show that very dry mixes in asphalt pavements are likely to have shorter performance lives.
Keywords: Asphalt content; Drier mixtures; Practical performance model; Hot mix asphalt; QC/QA; HMA; Engineering (0537)